EFFECT OF ORGANIC MANURE AMENDMENT SOILS ON UPTAKE OF Pb, Cd AND Zn IN SPINACH - Egwu, G. N.; Okunola, Oluwole J.; Ogwoke, K. C. (FUDMA JOURNAL OF SCIENCES, 2023)
Organic amendment of soil is an effective pathway of remediation of heavy metals in polluted agricultural soils and it is mostly carried out insitu, hence, this study aimed was to reestablished the remediation potentials of organic manure from different sources. Therefore, the study was conducted with spinach as the test crop to investigate the uptake of lead (Pb), cadmium (Cd) and zinc (Zn) from agricultural soils treated with poultry, cow and pig manure compost with different concentrations of the metals. The results showed that manure application decreased Cd content in the plant shoot. This indicated that application of manure compost reduced Cd concentration in the spinach. The lowest and highest available Pb content was found in soils treated with 30g and 10.71g of poultry droppings, respectively, this suggest low mobility of Pb in 30g compost manure compare to 10.71g compost manure. The lowest and highest available Zn content was found in soils treated with 30g and 7.14g of cow dung, respectively, although these materials contained the same concentration of Zn suggesting low mobility of Zn in soil with 30g cow dung compare with 7.14g cow dung. Generally, from the results, spinach showed its suitability for phytoextraction of Cd, Pb and Zn. However, application of organic manure could make spinach suitable for phytostabilization in a contaminated soil.